Microscopic mechanism of cellulose nanofibers modified cemented gangue backfill materials - Wu, J; Yang, S; Williamson, M; Wong, HS; Bhudia, T; Pu, H; Yin, Q; Ma, D; Chen, W (Springer, 2025)
Reinforcing the performances of cemented backfill materials to recycle gangue and tailings is crucial for the sustainable development of mineral resources and mining waste management. However, under practical constraints of low cost, high waste ratio, low carbon emission, and low binder consumption, solidifying upcycles of mining wastes with toxicity, porosity, and mollification to cemented backfill materials with superior properties are inherently contradictory and challenging. This study reported a waste-to-wealth pathway that improves cemented gangue backfill materials by cellulose nanofibers to recycle mining wastes and partially replace cement. Mechanical compression, X-ray diffraction, thermogravimetry, mercury intrusion porosimetry, scanning electron microscopy tests, fractal quantitative analyses of microstructures, and molecular dynamics simulations were carried out to reveal the action mechanism of TEMPO-modified cellulose nanofibers on cemented gangue backfill materials. The difference in the contribution of TEMPO-modified cellulose nanofibers and mechanical cellulose nanofibers to the strengths of cemented gangue backfill materials was analyzed. The results show a series of microscopic improvements of cellulose nanofibers on cemented gangue backfill materials, including regulating cemented gel polymerization, increasing hydration nucleation, inhibiting carbonization, densifying pore structure, enhancing Ca-O connections and H bonds, and preventing C-S–H fracture along interlayer water. Excessive cellulose nanofibers are also found to be harmful to this composite mainly by delaying hydration crystallization and increasing pores by entrapping air, while it still exhibits improvements in deformation resistance and energy absorption despite strength deterioration. The strength and energy absorption reinforcements of this cemented hybrid materials induced by cellulose nanofibers with optimal dosage can reach up to 30 ~ 50%.